DESIGN COORDINATION IN DISTRIBUTED ENVIRONMENTS USING VIRTUAL REALITY SYSTEMS - Rusdi HA (Institute of Research and Community Outreach - Petra Christian University, 2003)
This paper presents a research project, which investigates the use of virtual reality and computer communication technology to facilitate building design coordination in distributed environments. The emphasis of the system, called VR-based DEsign COordination (VRDECO) is providing a communication tool that can be used by remote designers for settling ideas before they fully engage in concurrent engineering environments. VRDECO provides the necessary design tools, library of building elements and communication procedures, for designers from remote places to perform and coordinate their initial tasks. It has been implemented using available commercial software packages, and is used in designing a simple house. VRDECO facilitates the creation a preliminary design and simple communication with the client. There are, however, some difficulties in the development of the full version of VRDECO, i.e.: creating an adequate number of building elements, building specification database with a sufficient number of choices, and establishing a systematic rule to determine the parts of a building that are updateable.